Health-related quality of life in people with type 1 Diabetes Mellitus: data from the Brazilian Type 1 Diabetes Study Group. Issue 1 (December 2015) - Braga de Souza, Ana; Felício, João; Koury, Camila; Neto, João; Miléo, Karem; Santos, Flávia; Negrato, Carlos; Motta, Ana; Silva, Denisson; Arbage, Thaís; Carvalho, Carolina; de Rider Brito, Hana; et al.
Abstract Background Type 1 Diabetes Mellitus (Type 1 DM) affects the psychological and emotional well-being of patients and their families. This study aims to evaluate the health- related quality of life (HRQoL) of people with Type 1 DM in Brazil, a country of continental proportions, using the EuroQol questionnaires. Methods This was a retrospective, cross-sectional, multicenter study performed by theBrazilian Type 1 Diabetes Study Group, by analyzing EuroQol scores from 3, 005 participants with Type 1 DM, in 28 public clinics in Brazil. Data on demography, economical status, chronic complications, glycemic control and lipid profile were also collected. Results The assessment of HRQoL by the EuroQol showed that the average score assigned to general health in Brazil is markedly lower than those found in two other Type 1 DM population-based studies conducted in Europe (EQ–VAS from the Netherlands, the United Kingdom and Brazil were 80.8 ± 15.2, 75.1 ± 18.4 and 72.5 ± 22, respectively). Additionally, our data suggest that a better glycemic control could positively impact the HRQoL of people with Type 1 DM, implying that each 1 % reduction in glycated haemoglobin might lead to an increase of 1.5 points in general health status assessed by the EuroQol. Conclusions This is a population-based study evaluating the HRQoL of people with Type 1 DM in Brazil. Our data indicate a worse quality of health of people with Type 1 DM in Brazil in comparison to Europe, and suggest that a better glycemic control could positively impact the HRQoL of these individuals. However, this study points to the existence of additional factors not yet evaluated that could be determinant in the HRQoL of these people.